Peritonitis due to Moraxella Osloensis: An Emerging Pathogen - Sreedhar Adapa; Purva Gumaste; Venu Madhav Konala; Nikhil Agrawal; Amarinder Singh Garcha; Hemant Dhingra (Case Reports in Nephrology)
Peritonitis is a very serious complication encountered in patients undergoing peritoneal dialysis and healthcare providers involved in the management should be very vigilant. Gram-positive organisms are the frequent cause of peritonitis compared to gram-negative organisms. There has been recognition of peritonitis caused by uncommon organisms because of improved microbiological detection techniques. We report a case of peritonitis caused by Moraxella osloensis (M. osloensis), which is an unusual cause of infections in humans. A 68-year-old male, who has been on peritoneal dialysis for 2 years, presented with abdominal pain and cloudy effluent. Peritoneal fluid analysis was consistent with peritonitis and peritoneal fluid culture grew gram-negative bacteria. M. osloensis was identified by 16 S PCR phenotypic and sequencing techniques. Patient responded well to the treatment, with intraperitoneal cephalosporin, and repeat peritoneal fluid culture yielded no growth. M. osloensis rarely causes infection in humans and responds well to treatment, as reported in literature.